lnc-REG3G-3-1/miR-215-3p Promotes Brain Metastasis of Lung Adenocarcinoma by Regulating Leptin and SLC2A5 - Jiang, Chunyang; Zhao, Hui; Yang, Bingjun; Sun, Zengfeng; Li, Xin; Hu, Xiaoli (Frontiers in Oncology, 2020)
This study aims to explore the role and mechanism of specific lncRNA in brain metastasis (BMs) from lung adenocarcinoma (LADC), providing an effective biomarker for early diagnosis and targeted therapy of BMs from LADC. Based on the gene expression profiles of lncRNA and mRNA in LADC and BMs tissues detected by Gene Chip, lnc-REG3G-3-1 was selected, and the related genes, including miR-215-3p, leptin, and SLC2A5, were identified by data analysis. Human LADC cell lines A549 and H1299 were cultured. Dual-luciferase and endogenous validation experiments were used to confirm the regulation between these genes. Real-time quantitative reverse transcription–polymerase chain reaction and Western blotting were used to detect gene expression. The tumor metastasis-related gene function of lnc-REG3G-3-1 and miR-215-3p in H1299 cells was verified by Transwell invasion, migration assays, and scratch testing. Nude mice xenograft tumors constructed with decreased lnc-REG3G-3-1 confirmed the influences on gene expression in vivo. lnc-REG3G-3-1 was highly expressed in BM tissues that originated from LADC compared with that in primary cancer tissues. lnc-REG3G-3-1 reduced miR-215-3p expression, thereby regulating the target genes leptin and SLC2A5 and the signaling pathways, taking part in the lnc-REG3G-3-1/miR-215-3p axis in the process of BM from LADC. lnc-REG3G-3-1, leptin, and SLC2A5 through regulating signaling pathways may be jointly involved in the regulation of the biological process of BM in patients with LADC.